EFEKTIVITAS PENGGUNAAN MEDIA LEAFLET TERHADAP HASIL BELAJAR EKONOMI KELAS XI IIS SMA SANTUN UNTAN - Oktaviani Oktaviani; Khosmas Khosmas; Bambang Genjik (Universitas Tanjungpura, 2020)
Abstract This study aimed to determine the effectiveness of the use of media leaflets on economic learning outcomes in class XI students of SMA SANTUN UNTAN. The method used in this study was the experimental method. The sample in this research was the students of senior high school of class XI IIS SANTUN UNTAN with a total number of students is about 30. While the number of questions was about 23 items, with an average learning rate of 70.03 students. After the media leaflet experiment showed a score of 83.17. Comparison of learning outcomes seen from the results of the test using SPSS 23 (0,000) was smaller than 0.05 = 5% or (0,000 <0.05) decision making with probability. Based on these results above, Ho is not effective and Ha is effective. Based on the results of these data it can be concluded that the LEAFLETS MEDIA was effective on learning outcomes of students in class XI IIS SMA UNTAN.Keywords: Economic leaflet learning lessons media Outcomes.